2013
DOI: 10.5194/nhess-13-3369-2013
|View full text |Cite
|
Sign up to set email alerts
|

Assessing institutional capacities to adapt to climate change: integrating psychological dimensions in the Adaptive Capacity Wheel

Abstract: Abstract. Several case studies show that social factors like institutions, perceptions and social capital strongly affect social capacities to adapt to climate change. Together with economic and technological development they are important for building social capacities.However, there are almost no methodologies for the systematic assessment of social factors. After reviewing existing methodologies we identify the Adaptive Capacity Wheel (ACW) by Gupta et al. (2010), developed for assessing the adaptive capaci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 35 publications
(62 reference statements)
0
39
0
Order By: Relevance
“…The implications of this gap in examining differential perceptions are critical to address since insights into risk perception can help identify entry points into incentivising adaptive behaviour. More recently, researchers have focussed on the implications of perceptions on adaptive action (Eakin et al 2016;Grothmann et al 2013) and demonstrated how socio-cultural factors, and policy and institutional environments mediate the translation of risk perceptions into response behaviour (Burnham et al 2016;Eakin et al 2016;Nguyen et al 2016). We argue that revisiting frameworks that seek to understand how and why perceptions of water risk differ and translate into differential behaviour is important to manage or respond to future risk.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The implications of this gap in examining differential perceptions are critical to address since insights into risk perception can help identify entry points into incentivising adaptive behaviour. More recently, researchers have focussed on the implications of perceptions on adaptive action (Eakin et al 2016;Grothmann et al 2013) and demonstrated how socio-cultural factors, and policy and institutional environments mediate the translation of risk perceptions into response behaviour (Burnham et al 2016;Eakin et al 2016;Nguyen et al 2016). We argue that revisiting frameworks that seek to understand how and why perceptions of water risk differ and translate into differential behaviour is important to manage or respond to future risk.…”
Section: Introductionmentioning
confidence: 91%
“…Other frameworks highlight how adaptive behaviour is driven by socio-cultural context (Adger et al 2013;Arunrat et al 2017;Feng et al 2017;Feola et al 2015;Nguyen et al 2016), actors external to the decision makers themselves (Feola et al 2015), the institutional environment (Eriksen et al 2015;Nguyen et al 2016), individual cognitive influences (Grothmann et al 2013;Eakin et al 2015;Singh et al 2016), and notions of identity and place (Marshall et al 2012;Singh 2014). Social memory also plays a role in community resilience through individuals (personal life histories) and stakeholder groups (collective memory) (Olick and Robbins 1998).…”
Section: Conceptualising Perceptions Of Riskmentioning
confidence: 99%
“…A large strand of adaptation research has focused on assessing vulnerability as a precondition for understanding adaptation needs (Grothmann et al 2013;de Sherbinin et al 2019;Woroniecki et al 2019). In the terminology of the ESG framework, this research has been interested in how climate change affects basic needs, as well as how adaptation can minimize adverse effects of climate change and safeguard access to basic needs.…”
Section: Access To Basic Needsmentioning
confidence: 99%
“…This might be a useful approach for understanding the local contexts as well as for developing capacities more effectively. Grothmann et al (2013) follow a similar line of argument and focus on how to integrate psychological components in the assessment of adaptive capacities of institutions. In their contribution they extend the adaptive capacity wheel by including "adaptation motivation" as well as "adaptation belief" of actors working in such different fields as water management, flood/coastal protection, civil protection and regional planning in their analysis.…”
Section: Social Capacities In the Context Of Vulnerability And Climatmentioning
confidence: 99%